1978
DOI: 10.1016/s0022-5347(17)57592-8
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin-Mediated Hypercalcemia in Transitional Cell Carcinoma of the Bladder

Abstract: A patient with known transitional cell carcinoma of the bladder and hypercalcemia was evaluated for urinary prostaglandin levels when no bone metastases or elevated parathormone levels could be demonstrated. Urinary levels of prostaglandin E metabolite were assessed in relation to serum and urinary calcium levels during treatment. The serum calcium levels decreased from the 13.0 mg. per cent range whenever the rpimary tumor was manipulated (transurethral resection) or when other treatments directed at the tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Mandell et al [13] and Beca-Giraudon et al [8] described increased levels of parathormone in 3 cases. In 2 other cases McKay et al [14] and Eddeland and Hedelin [5] found increased excre tion of prostaglandin in the urine in the presence of a normal parathormone level.…”
Section: Discussionmentioning
confidence: 93%
“…Mandell et al [13] and Beca-Giraudon et al [8] described increased levels of parathormone in 3 cases. In 2 other cases McKay et al [14] and Eddeland and Hedelin [5] found increased excre tion of prostaglandin in the urine in the presence of a normal parathormone level.…”
Section: Discussionmentioning
confidence: 93%